ACCOUNTING POLICY REGARDING THE PRODUCTIMYON AND SALE OF BEEKEEPING PRODUCTS - SULIMENKO, Larisa; MYKHALCHYSHYNA, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes approaches to the concept and content of individual components of the accounting policy of agricultural enterprises. It is determined that in order to determine the ways and methods of effective functioning of the beekeeping industry, stabilization, further development and increase of production efficiency, it is important to form reliable information on the volume of production, costs, income from the sale of products of enterprises in the industry, which is achieved by properly organized accounting. The expediency of forming an accounting policy for the production and sale of beekeeping products is determined. The goals and objectives of the accounting policy for the production and sale of beekeeping products in terms of applying principles, methods and procedures are substantiated. The factors that influence the formation of accounting policy for the production and sale of beekeeping products and are determined by the specifics of the industry are analyzed. These factors are grouped into three groups: administrative, organizational and technological. The first group includes government regulation of the industry and the taxation system. Organizational factors include the organizational and legal form of business, type of activity and size of the enterprise, management structure and form of accounting. Technological factors are determined by the seasonality of production, the duration of the production cycle, the receipt of main, related and by-products, and the internal use of manufactured products. It is stated that for beekeeping products, the elements of accounting policy for biological assets do not include the useful life and depreciation methods of long-term biological assets, the fair value of which cannot be reliably determined at the balance sheet date, since even in UAS 30 “Biological Assets” these accounting elements are not provided. The author investigates the problematic aspects of the accounting policy for the production and sale of beekeeping products and possible ways to eliminate them. The role of accounting policy for enterprises engaged in beekeeping should be considered in terms of organization of accounting, taxation and regulatory documents of the agricultural sector.
Keywords: accounting policy; accounting; biological assets; beekeeping products; principles; methods; procedures; production; realization; financial reporting